Intrahepatic fatty acids composition as a biomarker of NAFLD progression from steatosis to NASH by using 1H-MRS. Issue 72 (19th December 2019) - Xavier, Aline; Zacconi, Flavia; Gainza, Constanza; Cabrera, Daniel; Arrese, Marco; Uribe, Sergio; Sing-Long, Carlos; Andia, Marcelo E.
Abstract : Our results suggest that it would be possible to detect the progression of simple steatosis to NASH using 1 H-MRS. Abstract : Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in the world and it is becoming one of the most frequent cause of liver transplantation. Unfortunately, the only available method that can reliably determine the stage of this disease is liver biopsy, however, it is invasive and risky for patients. The purpose of this study is to investigate changes in the intracellular composition of the liver fatty acids during the progression of the NAFLD in a mouse model fed with Western diet, with the aim of identify non-invasive biomarkers of NAFLD progression based in 1 H-MRS. Our results showed that the intracellular liver fatty acid composition changes as NAFLD progresses from simple steatosis to steatohepatitis (NASH). Using principal component analysis with a clustering method, it was possible to identify the three most relevant clinical groups: normal, steatosis and NASH by using 1 H-MRS. These results showed a good agreement with the results obtained by GC-MS and histology. Our results suggest that it would be possible to detect the progression of simple steatosis to NASH using 1 H-MRS, that has the potential to be used routinely in clinical application for screening high-risk patients.